Pathophysiology and management of obesity related hypertension - Sharma, Arya (Henry Stewart Talks, 2007)
Prevalence of hypertension, Abdominal obesity and blood pressure, Myocardial infarction risk, Obesity and cardiovascular risk, Pathophysiology of obesity hypertension, Leptin, Cardiorenal effects of obesity, Renin-angiotensin system in obesity, Treatment of obesity hypertension, Currently approved anti-obesity agents: Orlistat and Sibutramine, Bariatric surgery